Comparative Analysis of the pIgR Gene from the Antarctic Teleost Trematomus bernacchii Reveals Distinctive Features of Cold-Adapted Notothenioidei - Alessia Ametrano; Simona Picchietti; Laura Guerra; Stefano Giacomelli; Umberto Oreste; Maria Rosaria Coscia (International Journal of Molecular Sciences, 2022)
The IgM and IgT classes were previously identified and characterized in the Antarctic teleost Trematomus bernacchii, a species belonging to the Perciform suborder Notothenoidei. Herein, we characterized the gene encoding the polymeric immunoglobulin receptor (pIgR) in the same species and compared it to the pIgR of multiple teleost species belonging to five perciform suborders, including 11 Antarctic and 1 non-Antarctic (Cottoperca gobio) notothenioid species, the latter living in the less-cold peri-Antarctic sea. Antarctic pIgR genes displayed particularly long introns marked by sites of transposable elements and transcription factors. Furthermore, analysis of T. bernacchii pIgR cDNA unveiled multiple amino acid substitutions unique to the Antarctic species, all introducing adaptive features, including N-glycosylation sequons. Interestingly, C. gobio shared most features with the other perciforms rather than with the cold-adapted relatives. T. bernacchii pIgR transcripts were predominantly expressed in mucosal tissues, as indicated by q-PCR and in situ hybridization analysis. These results suggest that in cold-adapted species, pIgR preserved its fundamental role in mucosal immune defense, although remarkable gene structure modifications occurred.